Evaluation of an Environmental Education Strategy on the Knowledge of Native Fauna Within the Framework of Folk Taxonomy - Salas-López, Gilbert Enrique (2021)
Since folk taxonomy is related to the innate classification of organisms, it could be the basis for designing, implementing, and evaluating environmental education strategies focused on biodiversity and its conservation. Through folk taxonomy, this study assessed a game-based environmental education intervention designed to improve Colombian native species’ knowledge. Two hundred and ninety-one (291) students from 4th to 9th grade of 11 public schools in Cundinamarca, Colombia, played ad libitum during the school recess period without a tutor. Students were asked to list all native Colombian animals they knew before playing for the first time and after having played for four to five weeks. The native animals mentioned were classified into the following ethnobiological taxonomic categories: life forms, generic, and specific. Although the composition of the “life forms” category did not change, there was a decrease in its abundance (taxa: two pre-game vs. two post-game; mentions: 101 pre-game vs. 89 post-game). Besides, there was an increase in composition and abundance in the “generic” category (taxa: 82 pre-game vs. 104 post-game; total 115; mentions: 2293 pre-game vs. 2505 post-game) and in the “specific” category (taxa: 24 pre-game vs. 53 post-game; total 64; mentions: 400 pre-game vs. 706 post-game). Because of the relation the relation between culture and the ethnobiological taxonomic categories, the decrease of abundance of taxa in the “life forms” category, and the increase of composition and abundance of taxa in the “generic” and “specific” categories, the results of this study can be considered as ideal for education interventions based on biodiversity and species identification.